Amos Decker : The Last Mile - Book 2 - Baldacci, David; Brewer, Kyf.; Cassidy, Orlagh (New York Hachette Audio, 2016)
"Convicted murderer Melvin Mars is counting down the last hours before his execution--for the violent killing of his parents twenty years earlier--when he's granted an unexpected reprieve. Another man has confessed to the crime."
Keywords: Football injuries -- Fiction; Memory -- Fiction; Murder -- Fiction -- Investigation; Police -- Fiction; Thrillers (Fiction); Audiobooks